Program Sosialisasi Pencegahan dan Deteksi Dini Kanker dan Pemeriksaan Kesehatan Pada PKK Desa Kragan, Gondangrejo - Nabilatul Fanny; Liss Dyah Dewi Arini; Annisa Yuli Kartika Sari; Muhammad Langlang Tahta Raharja (Jurnal Pengabdian Bidang Kesehatan, 2024)
The problem is that dangerous dust particles can cause health problems. Risk factors for cancer are free radicals, secondary lifestyle, lack of healthy food, and radiation exposure. Cancer has high morbidity and mortality. The aim of this community service activity is to increase optimal levels of health, to know about the prevention and early detection of cancer through healthy consumption patterns and appropriate physical activity as well as to increase people's knowledge, behavior and attitudes towards cancer problems and also to know the health conditions of residents based on the results. simple laboratory (weighing body weight, height, abdominal circumference, checking body temperature, checking oxygen levels in the blood, checking blood pressure, instant blood sugar, uric acid, cholesterol) to prevent the occurrence of non-communicable diseases (NCDs) at PKK RT 01 RW 002 Kragan Village, Gondangrejo. The result of the implementation of this community service is outreach to women from PKK PKK RT 01 / RW 02, Kragan village, Gondangrejo, which results in increasing knowledge regarding the prevention and early detection of cancer and health checks through simple laboratory checks for women from PKK PKK RT 01 / RW 02, Kragan village. , Gondangrejo can be used as a reference in knowing each individual's health, so that efforts can be made to maintain and maintain better health. The advice given in this community service activity is that to increase maximum results until there is a change in behavior in the community, a continuous health education program is needed so that it will motivate the community to carry out healthy behavior in order to improve the community's own health.